A Walking Controller for a Powered Ankle Prosthesis - Shultz, Amanda H. (Conf Proc IEEE Eng Med Biol Soc, 2014)
This paper describes a walking controller implemented on a powered ankle prosthesis prototype and assessed by a below-knee amputee subject on a treadmill at three speeds. The walking controller is a finite state machine which emulates a series of passive impedance functions at the joint in order to reproduce the behavior of a healthy joint. The assessments performed demonstrate the ability of the powered prosthesis prototype and walking controller to reproduce essential biomechanical aspects (i.e. joint angle, torque, and power profiles) of the healthy joint, especially relative to a passive prosthesis.